Modelling and Design of Inverter Threshold Quantization based Current Comparator using Artificial Neural Networks - Veepsa Bhatia; Neeta Pandey; Asok Bhattacharyya (Institute of Advanced Engineering and Science, 2016)
Performance of a MOS based circuit is highly influenced by the transistor dimensions chosen for that circuit. Thus, proper dimensioning of the transistors plays a key role in determining its overall performance. While choosing the dimension is critical, it is equally difficult, primarily due to complex mathematical formulations that come into play when moving into the submicron level. The drain current is the most affected parameter which in turn affects all other parameters. Thus, there is a constant quest to come up with techniques and procedure to simplify the dimensioning process while still keeping the parameters under check. This study presents one such novel technique to estimate the transistor dimensions for a current comparator structure, using the artificial neural networks approach. The approach uses Multilayer perceptrons as the artificial neural network architectures. The technique involves a two step process. In the first step, training and test data are obtained by doing SPICE simulations of modelled circuit using 0.18μm TSMC CMOS technology parameters. In the second step, this training and test data is applied to the developed neural network architecture using MATLAB R2007b.